Proposal of math activities to develop the process of teaching-learning in schoolchildren with severe mental retard - Blanca Rosa Fernández-Carela; Olga Lidia Carela-Martínez; Juan Enrique García-La Rosa (Maestro y Sociedad, 2018)
This research has as aim to devise a proposal of math activities that they guarantee to increase the development of knowledge, habits and skills that contribute to the development of teaching-learning process of Mathematics in the schoolchildren with severe mental retard. For that, it was selected a sample of schoolchild and teachers, equallythe methodological treatments, the systems of skills and the number of hour’s classes of the subject "Elementary Notions of Mathematics" were analyzed; andthey were conducted interviews to teachers and to the parents of schoolchildren. Analyzing these preliminary results it was elaborated 18 math activities, and they were subjected to valuation using empirical methods, that showed that they contribute to the development of the skills cognitive of the schoolchildren.